Secret of the wild child - Garmon, Linda; Estus, Boyd.; Keach, Stacy; Rymer, Russ.; WGBH (Television station : Boston, Mass.). Science Unit.; British Broadcasting Corporation. Television Service; WGBH Video (Firm); WGBH Educational Foundation; NDR International; Nederlandse Omroepprogramma Stichting ([South Burlington, VT] : WGBH Educational Foundation, 2006)
Examines the case of "Genie, " a girl whose parents kept her locked in a bedroom in total isolation, until she was discovered in 1970 at age 13. At first, her rehabilitation seemed to be an opportunity to test hypotheses of language acquisition, but disputes about the nature of her disabilities, the intensity of her therapy, and the progress of government funded research turned Genie's case into a sad example of the ethical quandaries of research on human subjects.
DVD, Dolby Digital.
Closed-captioned.
Narrator, Stacy Keach ; consultant, Boyd Estus.
Editor, Alexandra Anthony ; cinematographer, Don Lenzer, Boyd Estus ; sound mix, Richard Bock ; music composed and conducted by Elmer Bernstein ; additional music, Sheldon Mirowitz.
Based upon A silent childhood by Russ Rymer author of Genie: A scientific tragedy.
Special features: Printable materials for educators, access to the Nova website, scene selection.
Keywords: Psycholinguistics -- Case studies; Children -- Language -- Case studies; Sociolinguistics -- Case studies; Genie, -- 1957-; Abused children -- California -- Biography; Child development deviations; Language acquisition; Documentary television programs; Video recordings for the hearing impaired